The role of women in fish smoking processing and its impact on culinary tourism image in Malalanda Village, Kulisusu Districti - Rosmawati Rosmawati; Roslindah Daeng Siang; Irdam Riani; Wa Ode Piliana (Depik, 2025)
This study aims to analyze the role of women in promoting culinary tourism and to determine the production volume of smoked fish in Malalanda Village, Kulisusu District, North Buton Regency. The research was conducted from March to April 2024 using a purposive sampling method, considering the village's reputation for smoked fish production managed mostly by women. The population consisted of 19 female smoked fish processors, all of whom were selected as respondents through a census approach. Data were collected via interviews using questionnaires, direct observation, and secondary data from related institutions and literature. The results show that women are actively involved in all stages of smoked fish processing, including preparation, cleaning, sorting, smoking, cooling, and marketing. Production occurs up to 28 times per month, yielding a total of 14,334 pieces of smoked skipjack and tuna monthly. The highest individual output reached 952 fish per month, with an average of 796 fish per woman. These activities not only sustain culinary tourism but also contribute significantly to household income. The development of culinary tourism in the area highlights the vital economic role of women in local fisheries-based enterprises.Keywords:Culinary tourismIncomeSmoked fishWomen's roleWelfare